Efektivitas Penegakan Hukum Tambang Ilegal - Novia Rahmawati A Paruki; Ahmad Ahmad (Faculty of Law, Universitas Pattimura, 2022)
Indonesia is a country rich in mines, such as gold, silver, petroleum, mines, etc. Mining must be carried out by the government or the private sector. Every mining company is required to obtain a permit as regulated in Government Regulation Number 4 of 2009 concerning Mineral Mining in conjunction with Government Regulation Number 23 of 2010 concerning the Implementation of Mineral Mining. In fact, not all companies have a license. There are so many companies operating illegally. One of them is gold mining without a permit (illegal) in Tonala Village, Gorontalo Regency. The specification of this research is descriptive analytic. The method used is the normative as the primary approach and the juridical empirical method as the secondary approach. The data sources are secondary and primary. Data collection techniques used field studies with interviews for primary data and literature studies for secondary data. Then, the data were analyzed qualitatively in the form of qualitative descriptive.